The abundances and properties of Dual AGN and their host galaxies in the EAGLE simulations. Issue 2 (30th November 2018) - Rosas-Guevara, Yetli M; Bower, Richard G; McAlpine, Stuart; Bonoli, Silvia; Tissera, Patricia B
ABSTRACT: We look into the abundance of Dual AGN (active galactic nucleus) in the largest hydrodynamical simulation from the Evolution and Assembly of GaLaxies and their Environment (EAGLE) project. We define a Dual AGN as two active black holes (BHs) with a separation below 30 kpc. We find that only 1 per cent of AGN with L HX ≥ 10 42 erg s −1 are part of a Dual AGN system at z = 0.8–1. During the evolution of a typical binary BH system, the rapid variability of the hard X-ray luminosity on Myr time-scales severely limits the detectability of Dual AGN. To quantify this effect, we calculate a probability of detection, t on / t 30, where t 30 is the time in which the two BHs are separated at distances below 30 kpc and t on, the time that both AGNs are visible (e.g. when both AGNs have L HX ≥ 10 42 erg s −1 ) in this period. We find that the average fraction of visible Dual systems is 3 per cent. The visible Dual AGN distribution as a function of BH separation presents a pronounced peak at ∼20 kpc that can be understood as a result of the rapid orbital decay of the host galaxies after their first encounter. We also find that 75 per cent of the host galaxies have recently undergone or are undergoing a merger with stellar mass ratio ≥0.1. Finally, we find that the fraction of visible Dual AGN increases with redshift as found in observations.